2007
DOI: 10.1074/mcp.m600363-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional Blue Native/SDS Gel Electrophoresis of Multiprotein Complexes from Helicobacter pylori

Abstract: The study of protein interactions constitutes an important domain to understand the physiology and pathogenesis of microorganisms. The two-dimensional blue native/SDS-PAGE was initially reported to analyze membrane protein complexes. In this study, both cytoplasmic and membrane complexes of a bacterium, the strain J99 of the gastric pathogen Helicobacter pylori, were analyzed by this method. It was possible to identify 34 different proteins grouped in 13 multiprotein complexes, 11 from the cytoplasm and two fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 96 publications
(60 reference statements)
2
47
0
Order By: Relevance
“…Compared with the previous studies on the interactome of H. pylori using blue native two-dimensional gel or yeast twohybrid analysis (16,17) we found no interaction with incompatible cellular localization, i.e. between well defined cytoplasmic bait proteins and outer membrane or secreted proteins.…”
Section: Table I Tap-tagged Proteinsmentioning
confidence: 69%
See 3 more Smart Citations
“…Compared with the previous studies on the interactome of H. pylori using blue native two-dimensional gel or yeast twohybrid analysis (16,17) we found no interaction with incompatible cellular localization, i.e. between well defined cytoplasmic bait proteins and outer membrane or secreted proteins.…”
Section: Table I Tap-tagged Proteinsmentioning
confidence: 69%
“…Analyses of H. pylori protein complexes by blue native two-dimensional gel electrophoresis (17) are difficult to interpret because the resolution of the gels is limited, and hence the definition of a complex is relatively subjective. The authors of the latter study identified 13 multicomplexes among which the only overlap was UreA-UreB.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of its effective role for HP survival, urease is one of the most abundant proteins synthesized by HP (41). This protein has been already described in HP proteomes obtained from different gastric diseases (24,53). In particular, Pyndiah et al (53) showed a higher intensity of urease B (UreB) in HP isolates from patients with chronic gastritis or GC compared with isolates from patients with DU.…”
mentioning
confidence: 99%